Multilocus analyses indicate a mosaic distribution of hybrid populations in ground squirrels (genus Ictidomys). Issue 13 (11th October 2013) - Thompson, Cody W.; Anwarali Khan, Faisal Ali; Stangl, Frederick B.; Baker, Robert J.; Bradley, Robert D.
Abstract DNA sequence data from mitochondrial cytochrome‐b (Cytb) and Y‐linked structural maintenance of chromosomes (SmcY) genes were combined with 478 nuclear loci obtained from amplified fragment length polymorphisms (AFLP) to assess the extent of hybridization and genetic spatial structure of populations in two hybridizing species of ground squirrel (Ictidomys parvidens and Ictidomys tridecemlineatus). Based on AFLP analyses of 134 individuals from 28 populations, 10 populations were identified that possessed hybrid individuals. Overall estimates of FST values revealed strong support for population structure in the Cytb data set; however, analyses of the SmcY gene and the AFLP data indicated ongoing gene flow between species. Pairwise FST comparisons of populations were not significant for the SmcY gene; although they were significant for the Cytb gene, indicating that these populations were structured and that gene flow was minimal. Therefore, gene flow between I. parvidens and I. tridecemlineatus appeared to be restricted to populations that exhibited hybridization. In addition, the fragmented nature of the geographic landscape suggested limited gene flow between populations. As a result, the distributional pattern of interspersed parental and hybrid populations were compatible with a mosaic hybrid zone model. Because ground squirrels display female philopatry and male‐biased dispersal, the ecology of these species is compatible with this hypothesis.